Problematika Pembelajaran Di Madrasah Diniyah Nurul Jannah Di Dusun Rayung Desa Turirejo Kecamatan Kedamean Gresik - Aristawati, Fatika Maya; Sutono, Sutono; Suparno, Suparno (FATAWA: Jurnal Pendidikan Agama Islam, 2023)
In this research there are problems with the learning system at Madrasah Diniyah Awaliyah Dusun Rayung. This research uses descriptive qualitative research methods. Furthermore, the data required in this thesis consists of two types of sources, namely primary data sources and secondary data sources, these data sources include primary data sources or basic data sources originating from Madrasah Principals, teachers and educators or administrators of Madrasah Diniyah Awaliyah including foundations and secondary data sources or complementary data originating from parents/guardians of students. The instruments used to obtain data in the research, which is needed in preparing the thesis, are interviews and observations, namely in this research the instruments are used to obtain information about the problems of the Madrasah learning system. Diniyah Awaliyah and efforts to overcome it in Rayung Hamlet. The results of research on learning system problems faced by Madrasah Diniyah Awaliyah in Rayung Hamlet include: a) curriculum b) Material or Content c) Learning Methods d) Tools and Resources e) Facilities and Infrastructure f) Learning Media g) Evaluation and h) Teachers. Meanwhile, the efforts made to overcome the problems of the Diniyah Awaliyah Madrasah learning system in Dusun Rayung Village are adapting the material/content to student developments and needs and adapting the material/content to be updated at the current time. Improving teachers' learning methods by providing training in understanding and mastering various methods. Improving tools and resources by collaborating between Madrasah Diniyah Awaliyah and the community to improve tools and resources. Complementing inadequate facilities and infrastructure by looking for permanent donors and good cooperation in improving facilities and infrastructure. Improving learning media by means of teachers who teach at Madrasah Diniyah Awaliyah must be creative in using existing media. Improving evaluations that are far from standard values. Efforts to overcome evaluations are that teachers as evaluators are expected to be creative and understand assessments in the cognitive domain, affective domain and psychomotor domain and the efforts made to address teacher problems are to include teachers for upgrading and training.